Minimum Cost Flow Model and Algorithm of Virtual Network Embedding - Xiaohua Chen; Chunzhi Li; Liangyu Chen; Zhenbing Zeng (Dianxin kexue)
The dynamic process of network virtualization was studied,and the inversion phenomenon that the revenue did not rely on embedding cost was discovered.Then minimum cost flow model and algorithms of virtual network embedding which fit for creating virtual network online on the large-scale substrate network were proposed.Simulation results reveal that the proposed algorithms can improve virtual network acceptance ratio and system revenue,and significantly reduce the time complexity of multi-path virtual link embedding algorithm which ensures real-time performance of online virtual network embedding.The inversion phenomenon also occurs in the simulation.